Psychometric inspection of an internalized homonegativity measure - Kerry, Matthew James; Pfister, Andreas; Krüger, Paula (Frontiers in Psychology, 2025)
Internalized homonegativity (IH) is a substantively important construct linked to various health-related quality-of-life indicators. Despite IH’s prominence in the homosexuality literature, however, several measurement challenges are posed to advancing its empirical evidence base. This study aimed to bring modern psychometric methods to bear on a measure of IH in a general population sample of self-reported gay, lesbian, and bisexual respondents in Switzerland (n = 988). Specifically, we used a prospective observational cross-sectional design with questionnaire methodology to examine three aspects of the validity of a 7-item IH instrument: (1) structure validity, (2) cross-linguistic validity, and (3) “known-groups” (discriminant) validity. Our findings indicated support for the 7-item IH measure’s essential unidimensionality. Furthermore, we found support for IH’s measurement equivalence across German- and French-speaking regions, whereas mixed support was found for its extension to bisexual respondents. Finally, the IH measure exhibited discriminant validity, such that depression and poor self-reported health status were associated with higher IH scores. In conclusion, the IH instrument may be used as a unidimensional measure across German- and French-speaking general populations; however, further research should focus on extending its linguistic validity and measurement equivalence to bisexual and transgender populations.